"Análisis del gasto catastrófico en salud: una aproximación desde la estructura familiar, 2008 - 2019" - Calsin Perez, Ruth Alina (2020)
"Análisis del gasto catastrófico en salud: una aproximación desde la estructura familiar, 2008 - 2019"